2020
DOI: 10.2147/dddt.s276704
|View full text |Cite
|
Sign up to set email alerts
|

<p>In Vitro and In Vivo Rat Model Assessments of the Effects of Vonoprazan on the Pharmacokinetics of Venlafaxine</p>

Abstract: Purpose The purpose of the present study was to investigate the effects of vonoprazan on the pharmacokinetics of venlafaxine in vitro and in vivo. Methods The mechanism underlying the inhibitory effect of vonoprazan on venlafaxine was investigated using rat liver microsomes. In vitro, the inhibition was evaluated by determining the production of O-desmethylvenlafaxine. Eighteen male Sprague–Dawley rats were randomly divided into three groups: control group, vonoprazan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The results of in vitro studies indicated that vonoprazan could inhibit the metabolism of midazolam, the substrate of CYP3A4, and venlafaxine, the substrate of CYP3A4 and CYP2D6. In addition, the in vivo studies supported the results of the in vitro studies, which implicated the drug-drug interactions between vonoprazan and the substrates of CYP3A4 ( Chen et al, 2020 ; Wang et al, 2020 ). The half-maximal inhibitory concentration (IC50) value of CYP3A4 for vonoprazan was 29 μM, and this value is thought to be much higher than the plasma concentration of vonoprazan at clinical doses ( Nishihara et al, 2019 ).…”
Section: Introductionsupporting
confidence: 61%
“…The results of in vitro studies indicated that vonoprazan could inhibit the metabolism of midazolam, the substrate of CYP3A4, and venlafaxine, the substrate of CYP3A4 and CYP2D6. In addition, the in vivo studies supported the results of the in vitro studies, which implicated the drug-drug interactions between vonoprazan and the substrates of CYP3A4 ( Chen et al, 2020 ; Wang et al, 2020 ). The half-maximal inhibitory concentration (IC50) value of CYP3A4 for vonoprazan was 29 μM, and this value is thought to be much higher than the plasma concentration of vonoprazan at clinical doses ( Nishihara et al, 2019 ).…”
Section: Introductionsupporting
confidence: 61%
“…C804424, purity>98%) was purchased from Macklin (Shanghai, China). RLMs were prepared in our laboratory ( Chen et al, 2020 ; Zhou et al, 2020 ). HLMs were purchased from PrimeTox (Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
“…Venlafaxine (VLF) inhibits central 5-HT and NE neuronal reuptake, thereby increasing levels in the synaptic cleft between neurons in the brain. Oral VLF has low bioavailability, a short half-life, delayed onset of action, and significant systemic adverse reactions [ 105 , 106 ]. Cayero-Otero et al prepared VLF-loaded PLGA-NPs and modified the nanoparticles with transferrin and specific peptide against transferrin receptor.…”
Section: Intranasal Administration Of Antidepressant Active Ingredientsmentioning
confidence: 99%